Ultrasound evolution of parenchymal changes in the thyroid gland with autoimmune thyroiditis in children prior to the development of papillary thyroid carcinoma – a follow-up study - Januś, Dominika; Kujdowicz, Monika; Wójcik, Małgorzata; Taczanowska-Niemczuk, Anna; Kiszka-Wiłkojć, Aleksandra; Górecki, Wojciech; Starzyk, Jerzy B. (Frontiers in Endocrinology, 2023)
Papillary thyroid carcinoma (PTC) accounts for over 90% of all childhood thyroid cancer (TC) cases, and its incidence in paediatric patients is increasing. The objective of this study was to present the outcome of ultrasound (US) and laboratory monitoring of paediatric patients with autoimmune thyroiditis (AIT) prior to the development of PTC. Patients and methods: This study included 180 children (132 females; 73.3%) with a suspicion of thyroid disorder. The patients were divided into four groups: 1) 28 patients with a mean age of 10.7 [standard deviation (SD), 3.1] y, in whom PTC was detected during the active surveillance of AIT; 2) 18 patients with a mean age of 12.8 (SD, 3.4) y, in whom PTC and AIT were detected upon admission; 3) 45 patients with a mean age of 13.0 (SD, 3.4) y, in whom PTC was detected upon admission and AIT was excluded; and 4) an age- and sex-matched control group of 89 patients with AIT. The analysis included clinical, US, and laboratory assessment results of children on admission (groups 1–4) and during follow-up (groups 1 and 4). Results: PTC was diagnosed at the mean time of 3.6 y (3 mo–9 y) since AIT confirmation in group 1. US monitoring revealed an increase in thyroid echogenicity and an increased irregularity of the thyroid structure during the follow-up period of all of the patients from group 1. Such changes were not noticed in group 4. Interestingly, significant differences were observed in the thyroglobulin antibody (TgAb)/thyroid peroxidase antibody (TPOAb) ratio between groups 2 and 3, as opposed to group 4, at the beginning of observation. In group 1, after the follow-up, an increase in the TgAb/TPOAb ratio was observed [1.2 (9.8) to 5.2 (13.5)]. Conclusions: The use of thyroid US in the routine follow-up of patients with AIT may not only help with the early detection of thyroid malignancies that are not clinically apparent but also may influence the invasiveness of oncological therapy.We propose that the repeat evaluation of TPOAb and TgAb warrants further exploration as a strategy to determine TC susceptibility in paediatric patients with AIT in larger studies.